Stereoselective access to highly substituted vinyl ethers via trans-difunctionalization of alkynes with alcohols and iodine(III) electrophile - Ding, Wei (2020)
A method for the regio- and stereoselective synthesis of highly substituted vinyl ethers via trans-1,2-difunctionalization of alkynes with a cyclic λ3-iodane electrophile (benziodoxole triflate) and alcohols is reported. The reaction tolerates a variety of internal and terminal alkynes as well as various alcohols, affording β-λ3-iodanyl vinyl ethers in good yields with high regio- and stereoselectivities. The benziodoxole moiety of the products can be used as a versatile linchpin for the synthesis of structurally diverse vinyl ethers that are difficult to access by other means.